2021
DOI: 10.1111/bcpt.13550
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates renal interstitial fibrosis by regulating autophagy and retaining mitochondrial function in unilateral ureteral obstruction rats

Abstract: Renal interstitial fibrosis (RIF) is the leading cause of end‐stage renal disease, partly because of the lack of effective treatments. Curcumin, the primary active ingredient in turmeric, reportedly exerts potent antifibrotic effects. This study investigated the effects of curcumin on RIF in unilateral ureteral obstruction (UUO) rats and characterized the underlying action mechanism. UUO rats were treated with curcumin for 7 and 14 d. Renal fibrosis was evaluated through haematoxylin‐eosin staining, Masson sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Curcumin is the main active component in Curcumaelongae Rhizoma, which has been demonstrated to have an excellent anti-fibrotic effect. It was found that mitochondrial dysfunction was significantly improved in renal interstitial cells of UUO rats after curcumin treatment, which in turn inhibited the activation of NLRP3 inflammasome and the expression of PI3K/AKT/mTOR signaling pathway, alleviating the progression of renal fibrosis by reducing the inflammatory response and regulating autophagy [ 42 ]. Curcumin can also attenuate EndMT and fibrosis occurring after kidney transplantation, which is similarly accomplished by activating cellular autophagy [ 43 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…Curcumin is the main active component in Curcumaelongae Rhizoma, which has been demonstrated to have an excellent anti-fibrotic effect. It was found that mitochondrial dysfunction was significantly improved in renal interstitial cells of UUO rats after curcumin treatment, which in turn inhibited the activation of NLRP3 inflammasome and the expression of PI3K/AKT/mTOR signaling pathway, alleviating the progression of renal fibrosis by reducing the inflammatory response and regulating autophagy [ 42 ]. Curcumin can also attenuate EndMT and fibrosis occurring after kidney transplantation, which is similarly accomplished by activating cellular autophagy [ 43 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…Exogenous H 2 S also promoted autophagy by upregulating the expression levels of autophagy biomarkers, including LC3, Atg3, Atg5, Atg7, Atg12 and Atg16 [83]. Deregulated autophagy has been reported to be involved in renal fibrosis [84]. Therefore, it can be inferred that autophagy activation may mediate the effects of exogenous H 2 S on diabetes-induced renal fibrosis.…”
Section: Exogenous H 2 S Plays An Important Role By Regulating Autophagy In Diabetic Renal Fibrosismentioning
confidence: 96%
“…This difference may be related to the course and stage of diabetic nephropathy. Moreover, exogenous H 2 S reduced the expression levels of TGFβ1, nuclear factor of kappa B (NF-κB) and AKT in diabetic kidney tissue, suggesting the TGFβ1, NF-κB and AKT pathways may mediate the effects of exogenous H 2 S on autophagy in improving diabetes-induced renal fibrosis [84], which needs further studies, such as studies using an inhibitor to suppress the TGFβ1, NF-κB and AKT pathways.…”
Section: Exogenous H 2 S Plays An Important Role By Regulating Autophagy In Diabetic Renal Fibrosismentioning
confidence: 99%
“…Curcumin is a natural polyphenol product derived from the rhizome of the Curcuma longa, exerting anti-inflammatory, antioxidative, anti-tumor, and anti-fibrotic effects [ 131 ]. The presence of conjugated double bonds in the curcumin structure allows it to donate an electron and scavenge ROS [ 132 ].…”
Section: Antioxidants and Kidney Diseasesmentioning
confidence: 99%
“…In this study, curcumin inhibited the PI3K/Akt mammalian target of the rapamycin (mTOR) signaling pathway activation and upregulated essential proteins, mediating autophagosome formation. This led to suppressing the inflammatory response and mitochondrial dysfunction development [ 131 ]. Furthermore, the ability of curcumin to boost mitochondrial biogenesis warrants its exploration and use for renal disease [ 146 ].…”
Section: Antioxidants and Kidney Diseasesmentioning
confidence: 99%